Welfare of ducks, geese and quail on farm - EFSA Panel on Animal Health and Animal Welfare (AHAW Panel); Søren Saxmose Nielsen; Julio Alvarez; Dominique Joseph Bicout; Paolo Calistri; Elisabetta Canali; Julian Ashley Drewe; Bruno Garin‐Bastuji; Jose Luis Gonzales Rojas; Christian Gortázar Schmidt; Mette Herskin; Virginie Michel; et al. (EFSA Journal, 2023)
Abstract This Scientific Opinion concerns the welfare of Domestic ducks (Anas platyrhynchos domesticus), Muscovy ducks (Cairina moschata domesticus) and their hybrids (Mule ducks), Domestic geese (Anser anser f. domesticus) and Japanese quail (Coturnix japonica) in relation to the rearing of breeders, birds for meat, Muscovy and Mule ducks and Domestic geese for foie gras and layer Japanese quail for egg production. The most common husbandry systems (HSs) in the European Union are described for each animal species and category. The following welfare consequences are described and assessed for each species: restriction of movement, injuries (bone lesions including fractures and dislocations, soft tissue lesions and integument damage and locomotory disorders including lameness), group stress, inability to perform comfort behaviour, inability to perform exploratory or foraging behaviour and inability to express maternal behaviour (related to prelaying and nesting behaviours). Animal‐based measures relevant for the assessment of these welfare consequences were identified and described. The relevant hazards leading to the welfare consequences in the different HSs were identified. Specific factors such as space allowance (including minimum enclosure area and height) per bird, group size, floor quality, characteristics of nesting facilities and enrichment provided (including access to water to fulfil biological needs) were assessed in relation to the welfare consequences and, recommendations on how to prevent the welfare consequences were provided in a quantitative or qualitative way.